Observation of a nonlocal conductivity in the mixed state of YBa2Cu3O7-d: Experimental evidence for a vortex line liquid - Nieva, Gladys (1994)
Fil: Lopez, D. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina